(untitled) (Praxis Educativa, 2025)
The article discusses an educational research experience at a technical High School in Mar del Plata which, in the context of a research project, has become particularly expressive of an alternative way of doing—and living—research. Rooted in critical theory, the decolonial turn and queer theories, as well as in the entanglements of these perspectives with feminisms, race studies, posthumanism, queer phenomenology, agential realism, vitalism and the affective, pedagogic and ontological turns, we proceed by describing the forces that legitimize the disengagement from the modern-colonial power regimes that govern traditional science in an effort to explore their complicity with truth-making in a damaged world that is calling for change. Then, a particular research experience at the High School is discussed, where some ethical and methodological virtues are exposed; these result promising in the genesis of new academic environments, with greater sensitivity regarding contemporary indignities. The text advocates for tiny and local movements that can upset the cruelty axiomatic that characterizes the production of the present, in favor of gestures that can bring about alternative ways of being-doing research.